2016
DOI: 10.1021/acsami.6b04522
|View full text |Cite
|
Sign up to set email alerts
|

Giant Surface Conductivity Enhancement in a Carbon Nanotube Composite by Ultraviolet Light Exposure

Abstract: Carbon nanotube composites are lightweight, multifunctional materials with readily adjustable mechanical and electrical properties-relevant to the aerospace, automotive, and sporting goods industries as high-performance structural materials. Here, we combine well-established and newly developed characterization techniques to demonstrate that ultraviolet (UV) light exposure provides a controllable means to enhance the electrical conductivity of the surface of a commercial carbon nanotube-epoxy composite by over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The SEM images showed the formation of a MWCNT surface layer on the sample (Figure 6). In a previous study, the electrical conductivity of the MWCNT surface layer after UV degradation was found to be five times greater than that of the bulk 3.5 % MWCNT nanocomposite [49]. A roughly similar thickness of the MWCNT surface layer was observed after UV irradiation in this study for two doses: 775 MJ/m 2 (data not shown) and a much higher dose of 4865 MJ/m 2 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The SEM images showed the formation of a MWCNT surface layer on the sample (Figure 6). In a previous study, the electrical conductivity of the MWCNT surface layer after UV degradation was found to be five times greater than that of the bulk 3.5 % MWCNT nanocomposite [49]. A roughly similar thickness of the MWCNT surface layer was observed after UV irradiation in this study for two doses: 775 MJ/m 2 (data not shown) and a much higher dose of 4865 MJ/m 2 .…”
Section: Resultssupporting
confidence: 83%
“…This finding suggests that the MWCNT surface layer was effectively shielding the epoxy matrix underneath from further degradation, thus limiting growth in the thickness of the MWCNT surface layer. Based on experimental evidence, theory, and simulation, the high electrical conductivity MWCNT surface layer formed by UV irradiation has been postulated as due to a combination of matrix removal and densification of the MWCNT-rich domains in the nanocomposites [49]. …”
Section: Resultsmentioning
confidence: 99%
“…28 (c) Dense cluster of multi-walled carbon nanotubes often observed in commercial nanotube materials. 41 (d) A sampling of globular proteins from the protein data bank. 43 holds to a good approximation, and we provide the effective scaling exponents ν eff in Table II.…”
Section: A Flexible Worm-like and Rod-like Polymers And Particlesmentioning
confidence: 99%
“…20 shows Li + MOTIS-based microscopy of a carbon nanotube-based composite, where charge-based contrast allows clear differentiation between the conducting carbon nanotube bundles and the insulating epoxy matrix. 161 Because the ion beam consists of positive ions, the insulating areas accumulate a net positive charge and hence do not readily release secondary electrons. This causes them to appear black.…”
Section: Motis Realizationsmentioning
confidence: 99%
“…Image is of a cleaved face tilted toward the beam by 8 degrees, and shows a carbon nanotube mat formed on the surface by UV exposures (see Ref. 161 ). …”
Section: Figmentioning
confidence: 99%